Assessment and Mapping of Ammonium Concentration in Swale along the Faculty of Civil Engineering and Built Environment and G3 Lake, Universiti Tun Hussien Onn Malaysia, (UTHM) - UMPI, JERRY; KHAMIDUN, Dr. MOHD HAIRUL BIN (Recent Trends in Civil Engineering and Built Environment, 2023)
Water contamination can occur in a variety distinct way, point source and non-point source which lead to the catchment by surface runoff. This study has shown that the presence of untreated ammonium in the swales at Faculty of Civil Engineering and Built Environment and G3 Lake, Universiti Tun Hussien Onn Malaysia. It is no doubt that this ammonium concentration presence in the swale, generated by urbanization and the rise in the quantity of impermeable surfaces like as buildings, roofs, highways, parking lots, and other transportation-related structures. It also caused by the pollutants including vehicle emission and maintenance such as grass cutting. The ammonium was successfully found as the result obtained from the laboratory experiment, in the swale along the Faculty of Civil Engineering and Built Environment and G3 Lake which illustrate the trend of concentration mapping to figure out which part of the swale sample site had the highest concentration. Surfer Software (V16) was used to develop spatial distribution mapping on the colour pattern which shows the ammonium concentration in each week by the number of all sampling point area was collected. The result of each parameter for ammonium ranged 0.01- 0.8 mg/L, DO ranged 5.83- 8.47 mg/L, turbidity ranged 0.97- 63.27 NTU, pH ranged 3.62- 6.94, temperature ranged 23.3-28.1 ̊ C and TDS ranged 100- 900. The outcome of this research could be to give insights about the adequacy of water for daily usage activities, reducing the environmental impact and exhibit the trend of ammonium in the swale for future reference.